Formability studies on plasma arc welded duplex stainless steel 2205 sheet. Issue 2 (19th February 2020) - Pramod, R.; Mohan Kumar, S.; Shanmugam, N. Siva; Vendan, S. Arungalai
Abstract: Sheet metal forming is cost‐effective manufacturing process and hold a significant key position in fabrication works. Welding being a popular technique the industries primarily prefer for joining of sheet metal formed parts. The inherent material properties changes at the weld metal and heat affected zone post welding process, hence the impact and changes on mechanical strength aspects need to be studied. The current study focuses on influence of plasma arc welding on formability of 1.6 mm thick duplex stainless steel 2205 sheet using Erichsen cupping test by gauging the height of the cup formed. The performed tests such as uniaxial tensile, microhardness showed better mechanical properties and decrease in formability noted from Erichsen cupping test for weld metal compared to base metal. Finite element analysis of Erichsen cupping test is conducted using ABAQUS software and results are matched with experimental outcomes for validation. The comparison shows that a deviation of less than 5 % is noticed between actual and predicted formability index values. Microstructure examination reveals that, equiaxed grains at the weld center and columnar grains at sides typically formed in the weld metal region. The decrease in formability of weld blank compared to base blank is attributed to an increase in ferrite content. This is supported by amount of ferrite content measured in weld metal is 55 % and base metal is 52 %. The scanning electron micrographs (base and weld blank) reveal the mode of failure is ductile. Abstract : The work is a contribution towards the improvement of knowledge on the effects of plasma arc welding on the formability of duplex stainless steel 2205. The reliability of predicted Erichsen cupping index value through finite element analysis is validated by experimental test. The science behind the changes in formability post welding process is discussed by supporting uniaxial tensile and hardness test. A scientific exploration in relation to metallurgical aspects is disclosed.